Using the method of integration for parts show that ∫xe^(x/2) dx = 2xe^(x/2) - 4e^(x/2) + constant

Expert Answers info

sciencesolve eNotes educator | Certified Educator

calendarEducator since 2011

write5,349 answers

starTop subjects are Math, Science, and Business

You need to remember the formula of integration by parts such that:

`int udv = uv - int vdu`

Selecting `u = x ` and `dv = e^(x/2)dx`  yields:

`u = x => du = dx`

`dv = e^(x/2)dx...

(The entire section contains 103 words.)

Unlock This Answer Now


check Approved by eNotes Editorial